PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PENGELOLAAN KEUANGAN MAHASISWA DI CIKARANG - Monika Kussetya Ciptani; Asni Anggraeni (Universitas Merdeka Madiun, 2023)
The economic development and the increase of student opportunity to work while studying college, leads to the importance of financial management. Many colleges student study and also have a work to increase their personal income and pay their tuition fee. Considering the circumstances, they should know about how to manage the personal income. Problem arise when students cannot manage their personal income because of their lack of financial literacy and their way of life (lifestyle). This study aims to examine the relationship between financial literacy and lifestyle towards student’s financial management at President University, Pelita Bangsa University, Cikarang Branch Open University, STAI HAS Cikarang, STEBI Global Mulia and LP3I Cikarang. This research is a descriptive quantitative research with data collection techniques using questionnaire, using sample of 150 students at President University, Pelita Bangsa University, Cikarang Branch Open University, STAI HAS Cikarang, STEBI Global Mulia and LP3I Cikarang. The data analysis technique uses the classical assumption test, multiple linear regression analysis, F test and T test. The results of this study is that financial literacy has a significant effect on students’financial management in Cikarang, while Lifestyle also has a significant effect on student financial management in Cikarang.